2021
DOI: 10.12688/wellcomeopenres.16655.2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and validation of trans-valvular flow derived by four-dimensional flow cardiovascular magnetic resonance imaging in patients with atrial fibrillation

Abstract: Background: Four-dimensional (4D) flow cardiovascular magnetic resonance imaging (MRI) is an emerging technique used for intra-cardiac blood flow assessment. The role of 4D flow cardiovascular MRI in the assessment of trans-valvular flow in patients with atrial fibrillation (AF) has not previously been assessed. The purpose of this study was to assess the feasibility, image quality, and internal validity of 4D flow cardiovascular MRI in the quantification of trans-valvular flow in patients with AF. Methods: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Automated retrospective valve-tracking on long-axis four-chamber orthogonal cine views was carried out using CAAS MR software during image post-processing. This was performed using recently published and well-established methods (15)(16)(17) (Figure 1 and 2). After manual correction of any misalignment between the 4D flow CMR data and the cine images, automated tracking of mitral inflow allowed for careful isolation of transvalvular forward flow through only the mitral valve and into the left ventricle during diastole.…”
Section: Automated Dynamic Methods and Static Planar Methodsmentioning
confidence: 99%
“…Automated retrospective valve-tracking on long-axis four-chamber orthogonal cine views was carried out using CAAS MR software during image post-processing. This was performed using recently published and well-established methods (15)(16)(17) (Figure 1 and 2). After manual correction of any misalignment between the 4D flow CMR data and the cine images, automated tracking of mitral inflow allowed for careful isolation of transvalvular forward flow through only the mitral valve and into the left ventricle during diastole.…”
Section: Automated Dynamic Methods and Static Planar Methodsmentioning
confidence: 99%
“…Retrospective valve tracking can be applied in patients with atrial fibrillation [ 76 ]. However, a cautious approach should be used as there is a possibility of underestimating flows.…”
Section: Clinical Post-processing Workflowmentioning
confidence: 99%
“…Furthermore, as all the measurements are obtained from the same acquisition, the impact of variability related to changes in heart rate, on consistency of measurements will be reduced [ 28 ]. Although blurring can occur as a result of irregular heart rate [ 29 ], recent study showed that measurements of flow volumes remain accurate and feasible even in the presence of atrial fibrillation [ 30 ]. Moreover, peak velocity measurements in stenotic lesions may be more accurate and precise than with PCMR [ 31 ].…”
Section: Introductionmentioning
confidence: 99%